1990
DOI: 10.1111/j.1365-2044.1990.tb14787.x
|View full text |Cite
|
Sign up to set email alerts
|

Introducing patient‐controlled analgesia for postoperative pain control into a district general hospital

Abstract: SummaryPatient-controlled analgesia was introduced in a district general hospital in order to improve postoperative pain control. Techniques of management were developed with effectiveness, safety and practicality as the main objectives. An analysis of the first 1000 patients to use the system is presented. Problems were encountered with slow respiratory rate, monitoring, equipment function and ward management. Identijication of specijic hazards and management problems led to improvements in system safety. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…5 Although i.v. PCA represents a well-accepted and satisfactory means of acute pain treatment, 6,7 individual case reports [8][9][10][11][12][13][14][15][16][17][18][19][20][21] and larger case series 8,22,23 have described the occurrence of i.v. PCA-related ADEs resulting from operator error, patient error, or device malfunction.…”
mentioning
confidence: 99%
“…5 Although i.v. PCA represents a well-accepted and satisfactory means of acute pain treatment, 6,7 individual case reports [8][9][10][11][12][13][14][15][16][17][18][19][20][21] and larger case series 8,22,23 have described the occurrence of i.v. PCA-related ADEs resulting from operator error, patient error, or device malfunction.…”
mentioning
confidence: 99%
“…While the number of reports of 'run-away' pumps, where the PCA pump unexpectedly delivers an unprescribed dose of drug (Notcutt & Morgan, 1990), has decreased following changes made to pump design, they continue to occur, including a report of spontaneous triggering (Christie & Cranfield, 1998) and of a frayed wire in the demand apparatus leading to triggering as a result of an electrical short circuit (Doyle & Vicente, 2001). …”
Section: Equipment-related Complicationsmentioning
confidence: 99%
“…However, several retrospective observational studies involving almost 10,000 adult patients showed an increased incidence of not only mild or moderate adverse events, such as nausea and sedation, but also severe adverse events, such respiratory depression with hypoxemia, with no increase in efficacy, with the addition of a background infusion. [3][4][5][6] The recently updated guidelines for perioperative pain management from the American Society of Anesthesiologists do not recommend the use of a background infusion, because there appears to be no additional analgesic benefit. 7 In contrast, BACKGROUND: Bolus administration of opioids via a patient-controlled analgesia (PCA) device is widely used in the postoperative pediatric population.…”
mentioning
confidence: 99%